A Development Approach to a Protracted IDP Situation: Lessons from Azerbaijan. (March 2023) - Wistrand, Jennifer S.
This article highlights the realities facing Azerbaijan's internally displaced persons (IDPs), living in a state of protracted displacement. It argues that the World Bank's development approach to the IDP population in Azerbaijan and to IDP populations elsewhere has likely done more for these populations' long-term welfare and prospects than exclusively humanitarian approaches could have accomplished, even though displaced peoples have traditionally been presumed to be the responsibility of the humanitarian community. The article begins with a brief discussion of the differences between refugees and IDPs and between humanitarian and development approaches. It then outlines a history of the conflict between Azerbaijan and Armenia over the contested region of Nagorno-Karabakh which, in the early 1990s, produced upward of a half-million Azerbaijani IDPs. Next, the article discusses some of the realities (economic, social, and mental health, among others) that confronted Azerbaijan's IDPs 15 years into their displacement. It focuses on a community of IDPs who lived in a temporary-turned-long-term "collective center" on the outskirts of Azerbaijan's capital of Baku. Finally, the article discusses one of the World Bank's projects in Azerbaijan with IDPs. The article concludes with policy recommendations on the way future scholars, practitioners, and policymakers should be trained to understand and approach IDPs. More broadly, it recommends that combined humanitarian and development approaches to IDP situations should become the norm. This seems imperative given that the number of IDPs displaced by conflict and violence world-wide has increased each year for more than a decade, while the ability of IDPs to avail themselves of traditional durable solutions has not kept pace.